Konstruksi Realitas Arogansi Patwal di Platform Digital: Analisis Framing Pemberitaan Kasus Patwal RI 36 di Media Online - Diana Sapitri; Ike Desi Florina; Didi Permadi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the construction of the reality of the arrogance of RI 36 Patwal officers on digital platforms through a framing analysis approach. Using a descriptive qualitative method, this research examines how social media and online reporting shape public perceptions of the incident. The data collected were narratives, news articles, posts, and comments on social media related to the patwal arrogance incident. The analysis was conducted using the agih method to examine framing elements, such as syntactic structure, vocabulary, and rhetoric in the text that lead to the formation of public opinion. The results showed that the framing formed by social media and online news was more dominant towards a negative perception of Patwal officers, highlighting arrogant actions as a symbol of abuse of power. Despite clarification efforts from related parties, the public opinion formed through the initial framing remains difficult to change. This research reveals how framing on digital platforms has a major influence in shaping social reality and perceptions of the actions of state apparatus.